2004
DOI: 10.1093/ps/83.12.1992
|View full text |Cite
|
Sign up to set email alerts
|

A dose-response study with the feed enzyme beta-mannanase in broilers provided with corn-soybean meal based diets in the absence of antibiotic growth promoters

Abstract: An experiment was designed to assess the effects of graded levels of beta-mannanase on performance and body weight uniformity of male broilers provided with diets based on corn and soybean meal and devoid of antibiotic growth promoters or coccidiostats. Four dietary treatments contained 0, 50, 80, and 110 MU of Hemicell/ ton (where 1 MU = 10(6) enzyme activity units, 100 MU/ton is manufacturer's recommendation). Each treatment contained 15 pens with 40 birds/pen. Individual bird weights were determined on d 0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
72
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(90 citation statements)
references
References 22 publications
16
72
0
2
Order By: Relevance
“…Lesson et al (1996); Augelovicova and Michalik (1997) on the other hand reported increases in feed intake as a result of enzyme supplementation due to increased nutrient digestibility. The improved feed conversion due to enzyme supplementation in the present study is in agreement with earlier findings (Wang et al, 1997;Huazhong et al, 1999;Jackson et al, 2004;Rahman et al, 2005;Zou et al, 2006;Onu et al, 2011). These researchers reported that exogenous enzymes greatly improved the feed conversion ratio of broiler chicks fed enzyme supplemented diet.…”
Section: Resultssupporting
confidence: 93%
“…Lesson et al (1996); Augelovicova and Michalik (1997) on the other hand reported increases in feed intake as a result of enzyme supplementation due to increased nutrient digestibility. The improved feed conversion due to enzyme supplementation in the present study is in agreement with earlier findings (Wang et al, 1997;Huazhong et al, 1999;Jackson et al, 2004;Rahman et al, 2005;Zou et al, 2006;Onu et al, 2011). These researchers reported that exogenous enzymes greatly improved the feed conversion ratio of broiler chicks fed enzyme supplemented diet.…”
Section: Resultssupporting
confidence: 93%
“…Whereas Jackson et al (2003Jackson et al ( , 2004 and Daskiran et al (2004) reported beneficial effects on BWG and FCR during starter and grower phases of growth from 80 or 110 unit/g β-mannanase supplementation. Similarly, Kidd et al (2001) fed broilers corn and soybean meal based diets with or without anα-galactosidase (112 g/ton) enzyme.…”
Section: Discussionmentioning
confidence: 98%
“…Lee et al (2005) reported that GM can be used at up to 5% with β-mannanase enzyme in broilers. Jackson et al (2004) reported that Hemicell improved weight gain and FCR of broilers.…”
Section: Discussionmentioning
confidence: 98%